Internet connectivity disruption in Peru (Peru) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Peru. Data sourced from IODA.
Network Disruption Incident ID: PE-2026-0014. Severity: critical. Confidence: 65%